Flexible rGO-SnO2 supercapacitors converted from pastes containing SnCl2 liquid precursor using atmospheric-pressure plasma jet. Issue 2 (15th January 2021) - Chang, Jung-Hsien; Lin, Ming-Feng; Kuo, Yu-Lin; Yang, Chii-Rong; Chen, Jian-Zhang
Abstract: Reduced graphene oxide (rGO)-SnO2 nanocomposites are fabricated on carbon cloth from screen-printed pastes containing rGO nanoflakes and SnCl2 liquid precursor by using a nitrogen atmospheric-pressure plasma jet (APPJ). RGO-SnO2 -coated carbon cloth is then used as the electrode of gel-electrolyte supercapacitors (SCs). Experiments conducted with various APPJ processing times suggest that the optimal APPJ processing time is 300 s. Cyclic voltammetry (CV) measurements indicate that 300-s APPJ processing results in the best areal capacitance of 97.53 mF/cm 2 . The capacitance retention rate is 85% after a 10, 000-cycle CV test. Further, capacitance increases by 11% after a 1000-cycle bending test under a bending radius of 7.5 mm, possibly owing to the better electrolyte/electrode contact and decrease in the charge transport resistance after mechanical bending. This study also characterized APPJ-processed rGO-SnO2 nanocomposites by scanning electron microscopy with energy dispersive spectroscopy, X-ray photoelectron spectroscopy, X-ray diffractometry, Raman spectroscopy, and water contact angle measurements.